Faculty of Civil Engineering - Celko, Jan (Communications - Scientific letters of the University of Zilina, 2003)
The Faculty is accredited to educate students in the field of civil engineering (transport structures for construction design, reconstruction and maintenance of railway tracks, roads, highways, urban roads, bridges and tunnels). There are more than 1,000 students at the Faculty in daily courses, 27 PhD. daily students and 43 PhD. students in external form. The students from abroad can participate in both forms of study. The Faculty solves theoretical problems of design for transport structures, modeling, strain analysis, computer-based strength calculations and traffic planning in its research and professional activities. Significant results are achieved in measuring and diagnostics of transport structures subjected to dynamic loading. Courses of study are realized in three levels: bachelor (3 years), master (2 years), PhD (3 years).